1990
DOI: 10.1159/000186177
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Accumulation of Vanadium in Patients on Chronic Hemodialysis Therapy

Abstract: Vanadium (V) has been reported to inhibit a number of enzyme activities such as those of Na+-K+-ATPase. The main excretory pathway of this element is via the kidney. These facts led us to study the V distribution in uremic patients. As a result, hemodialysis patients at our dialysis center exhibited extremely high levels of serum V (23.9 ± 11.3 ng/ml, n = 43) as compared with healthy adults. Nondialysis patients did not show increased serum V concentrations. The V contents were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Considering that vana date is 90% protein-bound, the compound is probably not dialyzable to a significant degree. In preliminary studies we have shown that in patients on hemodialysis detectable amounts of vanadate were found in the dialysate at 1,2 and 4 h as compared to 0 time [94], These observations require further study as some investigators have shown a decrease in serum vanadate after dialysis [95]. One explanation for these results could be due to difference in the vanadate content of the dialysate as the concentration of this element correlates with levels found in tap water.…”
Section: Vanadate and Uremiamentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that vana date is 90% protein-bound, the compound is probably not dialyzable to a significant degree. In preliminary studies we have shown that in patients on hemodialysis detectable amounts of vanadate were found in the dialysate at 1,2 and 4 h as compared to 0 time [94], These observations require further study as some investigators have shown a decrease in serum vanadate after dialysis [95]. One explanation for these results could be due to difference in the vanadate content of the dialysate as the concentration of this element correlates with levels found in tap water.…”
Section: Vanadate and Uremiamentioning
confidence: 99%
“…Also, serum values are probably not reflective of the levels as most of the element is inside the cells. Worldwide fluctuations of water vanadate levels have been noted [7,95]. The study of Tsukamoto et al [95] clearly showed that while serum vanadate was as much as 140 times greater in the end-stage renal disease patient as compared to healthy subjects, it was highly variable throughout Japan.…”
Section: Vanadate and Uremiamentioning
confidence: 99%
See 1 more Smart Citation
“…Urea, hydro gen ion, potassium, guanidino compounds [1], vanadium [2] are a few examples. High plasma concentrations of urea, albeit not im mediately fatal, cause vomiting, malaise, and platelet dysfunction [3,4], It therefore ap pears reasonable to call urea a uremic toxin.…”
Section: Small Uremic Toxinsmentioning
confidence: 99%
“…4 On the other hand, the excess intake of vanadium inhibits biosynthesis of blood cholesterol and enzyme activities, and some diseases are induced because vanadium can be accumulated in blood. [5][6][7] Therefore, the level of vanadium in drinking water must be strictly controlled. A maximum concentration for vanadium in drinking water is fixed in some countries.…”
Section: Introductionmentioning
confidence: 99%